Fungal Screening for Potential PET Depolymerization - Malafatti-Picca, Lusiane [UNESP]; Bucioli, Elaine Cristina [UNESP]; de Barros Chaves, Michel Ricardo; de Castro, Aline Machado; Valoni, Érika; de Oliveira, Valéria Maia; Marsaioli, Anita Jocelyne; Govone, José Silvio [UNESP]; de Franceschi de Angelis, Dejanira [UNESP]; Brienzo, Michel [UNESP]; Attili-Angelis, Derlene [UNESP] (MDPI, 2023)
Approximately 400 billion PET bottles are produced annually in the world, of which from 8 to 9 million tons are discarded in oceans. This requires developing strategies to urgently recycle them. PET recycling can be carried out using the microbial hydrolysis of polymers when monomers and oligomers are released. Exploring the metabolic activity of fungi is an environmentally friendly way to treat harmful polymeric waste and obtain the production of monomers. The present study addressed: (i) the investigation of potential of strains with the potential for the depolymerization of PET bottles from different manufacturers (crystallinity of 35.5 and 10.4%); (ii) the search for a culture medium that favors the depolymerization process; and (iii) gaining more knowledge on fungal enzymes that can be applied to PET recycling. Four strains (from 100 fungal strains) were found as promising for conversion into terephthalic acid from PET nanoparticles (npPET): Curvularia trifolii CBMAI 2111, Trichoderma sp. CBMAI 2071, Trichoderma atroviride CBMAI 2073, and Cladosporium cladosporioides CBMAI 2075. The fermentation assays in the presence of PET led to the release of terephthalic acid in concentrations above 12 ppm. Biodegradation was also confirmed using mass variation analyses (reducing mass), scanning electron microscopy (SEM) that showed evidence of material roughness, FTIR analysis that showed band modification, enzymatic activities detected for lipase, and esterase and cutinase, confirmed by monomers/oligomers quantification using high performance liquid chromatography (HPLC-UV). Based on the microbial strains PET depolymerization, the results are promising for the exploration of the selected microbial strain.
Keywords: biodegradation; enzymatic catalysis; polymers; terephthalic acid